2005
DOI: 10.1063/1.1997290
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation mechanism of the seed of tetrapod ZnO nanostructures

Abstract: Tetrapod zinc oxide (T-ZnO) nanorods have been synthesized by evaporation and recondensation of metallic Zn under ambient conditions. The total sizes of the T-ZnO nanostructures range from 300nmto15μm with leg diameters of about 30to650nm, depending on the deposition temperature. A detailed high-resolution electron microscopy analysis showed that the center core of T-ZnO nanorods consists of four hexagonal grains with a twinlike relation. The nucleation and growth mechanism has been generated on the basis of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
75
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 31 publications
13
75
0
Order By: Relevance
“…On the contrary, high laser powers (high temperatures) lead to a predominant formation of tetrapods. These results are in agreement with the growth mechanism reported by Ronning et al 39 . It is important to note that the rods on the tip of the precursor are only formed for high laser powers.…”
Section: Znosupporting
confidence: 83%
“…On the contrary, high laser powers (high temperatures) lead to a predominant formation of tetrapods. These results are in agreement with the growth mechanism reported by Ronning et al 39 . It is important to note that the rods on the tip of the precursor are only formed for high laser powers.…”
Section: Znosupporting
confidence: 83%
“…[2] In this work, we report the synthesis of tetrapodlike ZnSSe alloy nanostructures (T-ZnSSe) of different compositions by catalyst-free chemical vapor deposition (CVD) and the studies of their composition-dependent Raman scattering and cathodoluminescence (CL). Novel tetrapod-like structures, constructed from 1D nanorods, have been observed in almost all the binary II-VI compounds, [3][4][5][6][7][8][9][10][11][12] but have not been in their ternary alloys. It has also been demonstrated that these tetrapod nanocrystals have many potential applications in waveguides, [13] photodiodes, [14] transistors, [15] field emission devices, [16] gas sensors, [17] and biomolecule delivery.…”
mentioning
confidence: 99%
“…The arms are usually single crystal wurtzite with lattice parameters a = 0.25 nm and c = 0.52 nm. The structure of the nucleus is of some debate because for different tetrapod sizes and morphologies different conclusions about its core structure have been made [2].…”
Section: Introductionmentioning
confidence: 99%